A Review of the Anti-Inflammatory Effects of Rosmarinic Acid on Inflammatory Diseases - Luo, Chunxu; Zou, Lin; Sun, Huijun; Peng, Jinyong; Gao, Cong; Bao, Liuchi; Ji, Renpeng; Jin, Yue; Sun, Shuangyong (Frontiers in Pharmacology, 2020)
Inflammatory diseases are caused by abnormal immune responses and are characterized by an imbalance of inflammatory mediators and cells. In recent years, the anti-inflammatory activity of natural products has attracted wide attention. Rosmarinic acid (RosA) is a water-soluble phenolic compound that is an ester of caffeic acid and 3,4-dihydroxyphenyl lactic acid. It is found in many plants, such as the those of the Boraginaceae and Lamiaceae families. RosA has a wide range of pharmacological effects, such as anti-oxidative, anti-apoptotic, anti-tumorigenic and anti-inflammatory effects.The anti-inflammatory effects of RosA have been revealed through in vitro and in vivo studies of various inflammatory diseases such as arthritis, colitis and atopic dermatitis. This review aims to discuss the anti-inflammatory effects of RosA in inflammatory diseases and its underlying mechanisms.